Empirical analysis of military expenditures in nato nations - Jakub Odehnal; Jiří Neubauer; Aleš Olejníček; Jana Boulaouad; Lenka Brizgalová (Economies, 2021)
The aim of the article is to identify possible "follower" behaviour; it means to reveal countries following the average military burden of North Atlantic Treaty Organization (NATO) member states. To analyse the relationship between military expenditure of NATO member states and selected socio-economic variables (average military burden of NATO member states, gross domestic product, government expenditure (non-military), share of trade balance of gross domestic product and population), the Autoregressive Distributed Lag model has been used. The short-term results demonstrate follower behaviour, especially in the new NATO member states (effort to fulfil the commitment to spend 2% of gross domestic product on defence). The long-term results have revealed a positive relationship between military expenditures and the variable describing the average military burden of NATO member states in the traditional and also new NATO member states. A positive relationship between military expenditure and gross domestic product has also been observed in the majority of evaluated countries in the long-term model. The public good effect has been determined in six member states only, and the crowding out effect in five member states. A positive effect of the balance of trade on military expenditure has been observed in two countries only.
Keywords: 330; ARDL models; free-riding; military expenditures; public goods